SEASONAL CHANGE IN THE DIEL PATTERN OF THE PSEUDO-NITZSCHIA POPULATION IN THE CISADANE RIVER ESTUARY: RESPONSE TO THE CHANGES IN THE WATER’S PHYSICAL-CHEMICAL PARAMETERS - Rachman, Arief; Thoha, Hikmah (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2014)
Seasonal changes of Pseudo-nitzschia diel dynamics in an estuarine ecosystem have been known to be regulated by salinity, water temperature and nutrient dynamics. In this study, we aimed to investigate the effect of these physical-chemical factors on the diel pattern of the Pseudo-nitzschia population in the Cisadane River estuary.Plankton samples were collected from a diel station at two different periods, in the dry season (May-June) and thewet season (September). Plankton samplings were done in a 24 hour period with 3 hourly sampling intervals. The result showed a higher abundance of Pseudo-nitzschia in the dark-period during the dry season, while during the wet season the abundance was higher in the light-period. Nitrate and phosphate concentrations were suggested as important factors in facilitating Pseudo-nitzschia maxima. The low abundance of Pseudo-nitzschia in the estuarycould be due to the relatively low N:P ratio (<10). The results showed that the Cisadane River estuary was strongly influenced by seawater during the night and by freshwater during day. The GLM analysis suggested that there were changes in the species omposition of the Pseudo-nitzschia population in the ecosystem. The oligohaline species was found to be abundant in the dry season, the maxima occurred at night, which is probably related to a highermarine influence in the ecosystem. Conversely the polyhaline species was abundant in the wet season, with the maxima occurring during daylight, which might be related to a stronger freshwater influence in the ecosystem.